2000
DOI: 10.1017/s0889189300008535
|View full text |Cite
|
Sign up to set email alerts
|

Performance of reduced-tillage cropping systems for sustainable grain production in Maryland

Abstract: Sustainable production systems are needed to maintain soil resources and reduce environmental contamination on erodible lands that are incompatible with tillageintensive operations. A long-term cropping systems comparison was established at Beltsville, Maryland, on a site with 2 to 15% slope to evaluate the efficacy of sustainable strategies compatible with reduced-tillage systems. All systems followed a 2-year rotation of corn the first year and winter wheat followed by soybean the second year. Treatments inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In general, even average yields were reported to be little affected by organic and conventional management, being 13% lower for organic systems that combine crops with animals and 20% for organic systems without animals. A more thorough examination of the organic systems in the USA revealed that the total amount of nutrients applied was as high as or even higher than that in comparative conventional systems (Teasdale et al, 2000;Porter et al, 2003;Denison et al, 2004;Sanchez et al, 2004;Pimentel et al, 2005). Similar nutrient application rates have also been reported in other publications dealing with organic cropping systems in the USA (Lockeretz et al 1980;Liebhardt et al, 1989;Clark et al, 1999).…”
Section: Cropping System Studies In the Usasupporting
confidence: 69%
“…In general, even average yields were reported to be little affected by organic and conventional management, being 13% lower for organic systems that combine crops with animals and 20% for organic systems without animals. A more thorough examination of the organic systems in the USA revealed that the total amount of nutrients applied was as high as or even higher than that in comparative conventional systems (Teasdale et al, 2000;Porter et al, 2003;Denison et al, 2004;Sanchez et al, 2004;Pimentel et al, 2005). Similar nutrient application rates have also been reported in other publications dealing with organic cropping systems in the USA (Lockeretz et al 1980;Liebhardt et al, 1989;Clark et al, 1999).…”
Section: Cropping System Studies In the Usasupporting
confidence: 69%
“…However, there are successful examples of annual or biennial living mulches established after emergence of the main crop, which gives the main crop a competitive advantage (Scott et al 1987;Wall et al 1991). If living mulches are established before or after the main crop is planted, competition of the living mulch for water may reduce crop yields (Echtenkamp and Moomaw 1989;Eberlein et al 1992;Masiunas et al 1997;Teasdale et al 2000). Thus, it can be concluded that living mulches can severely compete with the main crop for water which is particularly problematic during a dry period.…”
Section: Competition Between Living Mulch and Main Cropmentioning
confidence: 99%
“…A number of studies have shown that, under drought conditions, crops in organically managed systems produce higher yields than comparable crops managed conventionally. This advantage can result in organic crops out-yielding conventional crops by 70%-90% under severe drought conditions [122,124,[137][138][139]. The primary reason for higher yield in organic crops is thought to be due to the higher water-holding capacity of the soils under organic management, up to 100% higher in the crop root zone [13,116,122].…”
Section: Organic Farmingmentioning
confidence: 99%